Dendritic cell biology and its role in tumor immunotherapy - Wang, Yingying; Xiang, Ying; Xin, Victoria W.; Wang, Xian-Wang; Peng, Xiao-Chun; Liu, Xiao-Qin; Wang, Dong; Li, Na; Cheng, Jun-Ting; Lyv, Yan-Ning; Cui, Shu-Zhong; Ma, Zhaowu; et al. (Journal of hematology and oncology, 2020)
As crucial antigen presenting cells, dendritic cells (DCs) play a vital role in tumor immunotherapy. Taking into account the many recent advances in DC biology, we discuss how DCs (1) recognize pathogenic antigens with pattern recognition receptors through specific phagocytosis and through non-specific micropinocytosis, (2) process antigens into small peptides with proper sizes and sequences, and (3) present MHC-peptides to CD4 + and CD8 + T cells to initiate immune responses against invading microbes and aberrant host cells. During anti-tumor immune responses, DC-derived exosomes were discovered to participate in antigen presentation. T cell microvillar dynamics and TCR conformational changes were demonstrated upon DC antigen presentation. Caspase-11-driven hyperactive DCs were recently reported to convert effectors into memory T cells. DCs were also reported to crosstalk with NK cells. Additionally, DCs are the most important sentinel cells for immune surveillance in the tumor microenvironment. Alongside DC biology, we review the latest developments for DC-based tumor immunotherapy in preclinical studies and clinical trials. Personalized DC vaccine-induced T cell immunity, which targets tumor-specific antigens, has been demonstrated to be a promising form of tumor immunotherapy in patients with melanoma. Importantly, allogeneic-IgG-loaded and HLA-restricted neoantigen DC vaccines were discovered to have robust anti-tumor effects in mice. Our comprehensive review of DC biology and its role in tumor immunotherapy aids in the understanding of DCs as the mentors of T cells and as novel tumor immunotherapy cells with immense potential.